Pendampingan Psikologis Masyarakat Melalui Karakter Islami Pada Badan Pusat Kecemerlangan Diri Negeri Sembilan Malaysia - Andi Bunyamin; Akhmad Syahid; Abdul Wahab; Andi Bulqiah Nur Bunyamin; Junaedi; Lutfiah ur Huda Watri; Nur Aeni F (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This community engagement program was carried out at the Badan PusatKecemerlangan Diri (BPKD) in Seremban, Negeri Sembilan, Malaysia, with the aimof strengthening the psychological resilience of the local community through theinternalization of Islamic character values. The main problems identified include lowpsychological resilience, limited cultivation of Islamic character in daily life, lack ofIslamic-based psychological mentoring programs, limited capacity of facilitatorswithin BPKD, and the weak integration of spiritual and psychological aspects incharacter education. To address these issues, the program implemented astructured Islamic-based psychological mentoring model through psychoeducationgrounded in Islamic values, training of local facilitators, development of a psychosspiritual mentoring module, reflective classes and group guidance, communitybased learning groups, and systematic monitoring and evaluation. The resultsshowed an improvement in participants’ knowledge and skills in emotional andstress management, increased awareness of the importance of self-control andpatience, understanding of the concepts of tawakkul and riḍā in facing life pressures,and the emergence of daily practices that reinforce honesty, responsibility, andempathy. In addition to enhancing the psychological well-being and spiritualawareness of the participants, the program also empowered local facilitators toindependently continue the mentoring activities on an ongoing basis. Furthermore,this initiative helped strengthen the role of BPKD as a community-based institutionthat supports psychological and spiritual development through Islamic charactereducation.